Histopathological analysis of lymph nodes in patient with clinical lymphadenopathy - 266 cases - Patel, Komal; Patel, Mubin I.; Jha, Bharti M. (International Journal of Research in Medical Sciences, 2016)
Background: Lymphadenopathy is one of the most common clinical presentations among patients of all ages. This study has undertaken to study the histological patterns in various non-neoplastic condition, lymphoma and metastatic carcinoma in patient with lymphadenopathy and to do the clinico-pathological correlation with respect to age, sex and site of lymph node involved. Methods: Total 266 cases of lymph node biopsy were studied, for a period of 28 months at Pathology department, Government Medical College, Surat, Gujarat, India. Tissues were adequately fixed in formalin and blocks prepared, sections cut and slides were prepared, stained by routine H&E stain. A complete and thorough histopathological examination of all the slides was undertaken. Results: A total of 266 cases were studied, age range was 1-75 years, 136 were males and 130 were females. Out of 266 cases, 96 cases (36%) were non-specific lymph node hyperplasia, 81 cases (31%) were of metastatic deposits in lymph node, 70 cases (26%) were of specific non neoplastic conditions and 19 cases (7%) were of lymphoma. Conclusions: Lymph node biopsy plays an important role in establishing the cause of lymphadenopathy. Among the biopsied nodes, non-specific lymph node hyperplasia was the most common followed by metastatic deposits, specific non neoplastic conditions especially tuberculous lymphadenitis and lymphoma. Non neoplastic conditions were more common in early age while neoplastic conditions were more common in late age. TB lymphadenitis was more common in HIV positive patients as compared to general population.